In search of alternative models of integration: Europe as a club of clubs (Economic and Political Thought, 2015)
The vision of “Europe as a club of clubs” constitutes GiandomenicoMajone’s input into the discussion about the reform and future of the EuropeanUnion. Majone voices objections to further centralization and a transferof competences to the European level and calls for more differentiation(flexibility) of the integration process. The article discusses notions of differentiatedintegration and disintegration with regard to the EU and theirmutual relations as well as critical arguments against the current model ofEuropean integration based on the logic of neo-functionalism. Furthermore,the concept of change in the EU is outlined – from the model based onharmonization to the one based on cooperative competition. In conclusion,weaknesses of the “club of clubs” concept are indicated together with its positivecontribution to the redefinition of thinking about integration processesin Europe.